Answer :


Using the splitting middle term - the middle term of the general equation is divided in two such values that:


Product = a.c


For the given equation a = 9; b = -3; c = -2


= 9. - 2 = - 18


And either of their sum or difference = b


= - 3


Thus the two terms are - 6 and 3


Sum = - 6 + 3 = - 3


Product = - 6.3 = - 18




3x(3x-2) + 1(3x-2) = 0


(3x + 1)(3x-2) = 0


(3x + 1) = 0 or (3x-2) = 0


x = (-1)/3 or x = 2/3


Roots of equation are (-1)/3, 2/3


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Which of the follRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics